The Impact of Video Game Dimensions on Brand Love: A Guide for the Gaming Industry 2023-2024 - Youssef, Soliman Hamdy Hassan; Abdellatif, Alaa Tarek Khalil (Journal of Economic, Administrative and Legal Sciences, 2024)
This research paper investigates the factors contributing to brand love among gamers, with the aim of enhancing user experience and optimizing marketing strategies within the gaming industry. The study explores how specific gameplay elements and sensory triggers—such as rewards, personalization, music, and storytelling—affect emotional connections and foster brand loyalty. Additionally, it examines the application of neuromarketing techniques to gain a deeper understanding of consumer behavior and to promote stronger emotional engagement with gaming products, while also highlighting the importance of addressing ethical considerations and cultural differences in these strategies. Despite the growing popularity of video games, there is a notable lack of comprehensive research on the factors that elicit brand love, which limits developers’ and marketers’ ability to create engaging experiences that drive loyalty. Utilizing qualitative analysis involving professional gamers, developers, and bloggers, the study provides valuable insights for stakeholders aiming to develop more engaging and intuitive gaming experiences. It contributes to the academic literature on brand love and consumer behavior by identifying key dimensions of video games that evoke brand love. Specifically, the research focuses on: (1) analyzing how gameplay and sensory triggers enhance emotional connections, (2) exploring the impact of neuromarketing techniques on emotional responses, and (3) offering actionable recommendations for improving user experience and boosting customer loyalty. The major research question investigates which video game dimensions can trigger brand love, with subsidiary questions examining the effects of game and sensory triggers, and the potential role of neuromarketing in this context.